Syngas production by partial oxidation of ethanol on PtNi/SiO2–CeO2 catalysts. Issue 3 (8th January 2019) - Kraleva, Elka; Rodrigues, Clarissa P.; Pohl, Marga-Martina; Ehrich, Heike; Noronha, Fabio B.
Abstract : Syngas production from the partial oxidation of (bio)ethanol (POE) was demonstrated. Abstract : Syngas production from the partial oxidation of (bio)ethanol (POE) was demonstrated. For this purpose, Pt or Ni with different metal loading supported on CeSiO x were used as catalysts. The catalytic performance was studied in the 600–800 °C temperature range and with oxygen-to-ethanol molar ratios of 0.5 and 0.75. The highest ethanol conversion and H2 and CO selectivities were achieved at 800 °C. As byproducts, small amounts of CH4, C2 H4 O, and C2 H4 were found, and their selectivity decreased with increasing the reaction temperature. Carbon formation during POE at 800 °C on these catalysts followed the order: 1Pt/CeSiO x < 5Ni/CeSiO x < 1Pt5Ni/CeSiO x < 10Ni/CeSiO x < 1Pt10Ni/CeSiO x . Therefore, 1Pt5Ni/CeSiO x presented the best performance for the POE reaction at 800 °C, with low byproduct formation and carbon deposition, thus evidencing the cooperative effect of the support and the synergic effect between the Pt and Ni particles.